Probiotic supplement as a promising strategy in early tau pathology prevention: Focusing on GSK-3β? - Flynn, Cassandra M.; Yuan, Qi (Frontiers in Neuroscience, 2023)
Neurofibrillary tangles (NFT) is one of the hallmarks of Alzheimer’s disease (AD). Recent research suggests that pretangle tau, the soluble precursor of NFT, is an initiator for AD pathogenesis, thus targeting pretangle tau pathology may be a promising early intervention focus. The bidirectional communications between the gut and the brain play a crucial role in health. The compromised gut-brain axis is involved in various neurodegenerative diseases including AD. However, most research on the relationship between gut microbiome and AD have focused on amyloid-β. In this mini review, we propose to target preclinical pretangle tau stages with gut microbiota interventions such as probiotic supplementation. We discuss the importance of targeting pretangle tau that starts decades before the onset of clinical symptoms, and potential intervention focusing on probiotic regulation of tau hyperphosphorylation. A particular focus is on GSK-3b, a protein kinase that is at the interface between tau phosphorylation, AD and diabetes mellitus.